Prediction of performance in the 5,000 m run by means of laboratory and field tests in male distance runners - Pompcu, F. A.; Gomes, P. S.; Flegner, A. J. (Medicine & Science in Sports & Exercise, 1996)
Blood lactate curves during exercise have been widely used in the prescription of training stimuli for long-distance runners. Transferring laboratory results to field situations has been shown to be inadequate. It was found that running velocity at 4 mM/l fixed lactate concentration was the best predictor of performance in the 5,000 m run. Implication. A field test involving running was related more to 5,000 m running performance than physiological measures obtained in a laboratory gathered from a treadmill running task. Measures for prediction and analysis of sporting performance are best when they involve performing the activity itself.